(untitled) (American Journal of Physical Education and Health Science, 2024)
TKR One of the most popular and effective surgical procedures is total knee replacement (TKR), which significantly reduces pain and improves functional impairment in individuals with knee arthritis A number of psychological issues, such as depression, low self-efficacy, ineffective pain coping mechanisms, somatization, a lack of social support, and patient expectations occurs after a major surgery like TKR. This study aims to determine the level of psychological distress and pain threshold level among post-operative TKR patients. It was a cross sectional study with the sample size of 77. The subjects aged>40 years were enrolled, who had undergone the TKR procedure. After obtaining the informed consent form, the data was collected by filing the NPRS and HADS Performa from the enrolled subjects. Data was analysed via SPSS version 26. The subjects have the mean age of 55.55 with the standard deviation of 11.621. Pearson correlation test was applied to observe the correlation of time duration with NPRS and HADS which showed a negative correlation, interpreting that with the increase in time duration there is decrease in the scores of NPRS and HADS with the P-value of <0.05. There is a decrease in psychological distress with the increase in time duration in patients undergoing total knee replacement surgery. The current study reveals that with time, the level of pain and psychological distress, including anxiety and depression, as well as the pain threshold, decreases in the subjects who undergone through the TKR procedure.